Project Based Learning (PjBL) Model to Increase Motivation and Skills in Building Wireless Networks - Kurnia Dwi Ariyanti (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The low learning outcomes of students in the area-based network technology (WAN) subject in the matter of building a wireless network for class XI TKJ 1 students at SMKN 1 Trowulan became the background for this class action research. Researchers feel that the teaching and learning process is still centered on the teacher, material is often presented in the form of lectures and demonstrations so that researchers often find students are more silent and just listen, their creativity and independence are less realized and the teaching and learning process does not run as expected. This is the cause of student learning outcomes are still low. Through the results of class action research, namely by using the Project Based Learning (PjBL) learning model, there is an increase in motivation and skills in building wireless networks for class XI TKJ 1 students of SMK N 1 Trowulan in the even semester of 2021/2022, namely the motivation to build a wireless network with the title Very Good, which was originally 17%, increased to 20% and with a Good predicate, which was originally 46%, increased to 66%. While the results of learning/drawing skills, namely the highest score originally only 79 became 82, the lowest score which was originally 68 became 75 which means that all students passed the KKM, while the average which was originally 74.90 became 78.12.